2008
DOI: 10.1111/j.1601-183x.2008.00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of A2A receptors in anxiolytic, locomotor and motivational properties of ethanol in mice

Abstract: We have shown previously that mice lacking the adenosine A 2A receptor (A 2A R) generated on a CD1 background self-administer more ethanol and exhibit hyposensitivity to acute ethanol. We aimed to investigate if the increased propensity of A 2A 2/2 mice to consume ethanol is associated with an altered sensitivity in the motivational properties of ethanol in the conditioned place preference (CPP) and conditioned taste aversion (CTA) paradigms and with an altered development of sensitization to the locomotor eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…One study assessed the impact of deletions of A 2A R on the locomotor effects of acute alcohol administration; however, depending on the genetic background, increases in hyperactivity were noted in mice (mice generated on CD1 background) or no changes were noted (mice generated on C57BL/6J background). In addition, there was no effect of a lack of A 2A Rs in CD1 mice locomotor sensitization development induced by chronic ethanol administration [ 84 ]. In the use of nicotine, a pharmacological study showed that the A 2A R agonist CGS 21680 (0.2–0.4 mg/kg) inhibited, and the A 2A R antagonist KW 6002 (0.5 mg/kg) enhanced the acute locomotor effect of nicotine in rats.…”
Section: A 2a R and Behavioral Actions To Cocaimentioning
confidence: 99%
See 1 more Smart Citation
“…One study assessed the impact of deletions of A 2A R on the locomotor effects of acute alcohol administration; however, depending on the genetic background, increases in hyperactivity were noted in mice (mice generated on CD1 background) or no changes were noted (mice generated on C57BL/6J background). In addition, there was no effect of a lack of A 2A Rs in CD1 mice locomotor sensitization development induced by chronic ethanol administration [ 84 ]. In the use of nicotine, a pharmacological study showed that the A 2A R agonist CGS 21680 (0.2–0.4 mg/kg) inhibited, and the A 2A R antagonist KW 6002 (0.5 mg/kg) enhanced the acute locomotor effect of nicotine in rats.…”
Section: A 2a R and Behavioral Actions To Cocaimentioning
confidence: 99%
“…In studies on the rewarding effects of ethanol, CGS 21680 (0.5–1.0 mg/kg) reduced or did not affect the consumption and ethanol preferences in a two-bottle free-choice paradigm in mice [ 84 ]. In rats, a low dose of CGS 21680 (0.065 mg/kg) increased ethanol operant self-administration within non-dependent rats while higher CGS 21680 doses (0.095 or 0.125 mg/kg)—similar to the previous findings on mice—significantly reduced operant alcohol responses under FR1 within both non-dependent and dependent rats [ 102 ].…”
Section: A 2a R and Behavioral Actions To Cocaimentioning
confidence: 99%
“…In addition, an increasing body of evidence points to a direct role of adenosine in mediating some of the cellular and behavioral responses to ethanol [15, 40]. Caffeine and selective adenosine receptor antagonists reduce the duration of ethanol-induced loss of the righting reflex [38, 41], block the motor incoordination promoted by ethanol [5, 25, 42], and reverse retrograde memory impairment caused by a high dose of ethanol (3 g/kg) [27].…”
Section: Discussionmentioning
confidence: 99%
“…Deletion of the adenosine A 1 receptor did not alter operant responding for ethanol in B6 × 129 mice (Houchi, Persyn, Legastelois, & Naassila, 2013) (Table 5). Although male and female adenosine A 2A receptor (A2AR) knockout mice generated on a CD1 background drank more ethanol compared to wild-type in 2BC tests (Houchi et al, 2008; Naassila, Ledent, & Daoust, 2002), no differences were found between A2AR knockout and wild-type mice on a B6 background (Houchi et al, 2008). …”
Section: Neurotransmitter Systemsmentioning
confidence: 99%